Specific detection of the novel goose astrovirus using a TaqMan real-time RT-PCR technology - Wan, Chunhe; Chen, Cuiteng; Cheng, Longfei; Fu, Guanghua; Shi, Shaohua; Liu, Rongchang; Chen, Hongmei; Fu, Qiuling; Huang, Yu (Microbial pathogenesis, 2019)
Recently, a novel goose astrovirus (N-GoAstV) was discovered in China, with the transmission route of N-GoAstV unclear. In this study, we developed a TaqMan-based real-time RT-PCR (qRT-PCR) assay for the detection of N-GoAstV infection. After the optimization of the qRT-PCR assay conditions, the results demonstrated that the lower limit of detection for N-GoAstV was 33.4 copies/μL. No cross-reactivity was observed with other goose-origin viruses. Intra-assay and inter-assay variability were ≤1.36% and 2.34%, respectively. N-GoAstV was detected in both field samples, embryos and newly hatched goslings by qRT-PCR assay, provided the view that N-GoAstV may be both horizontally and vertically transmitted. The established qRT-PCR method showed high specificity, sensitivity, and reproducibility, which can be used in future investigations on the pathogenesis and epidemiology of N-GoAstV. •We established a TaqMan real-time RT-PCR method for detection of novel goose astrovirus (N-GoAstV).•The method showed high sensitivity, specificity and reproducibility for detection of N-GoAstV.•This study provided the view that N-GoAstV may be possible vertically transmitted.